Diagnóstico institucional del proyecto educativo de centro en el desarrollo de la educación intercultural - Segura Castillo, Mario (2011)
With the growing immigration taking place in Costa Rica, it is necessary to think about the development of strategic policies of intercultural education in order to give both better attention and living conditions to those who leave other regions of the world looking for better opportunities in our country. Besides, these strategies will support human rights from the point of view of the Costa Rican educational system. The PEC is an “instrument which collects and communicates an integral proposal to direct and guide coherently the processes of educative intervention that developed in a school intervention process.”(1992, p. 47). A research study is presented on the conditions of an educational center of and Cycles I and II of the Basic General Education. The study is based on an institutional diagnosis that was carried out to determine which conditions at this school favor or not the practice of the PEC. According to the opinions of students and teachers, the PEC focuses on intercultural education and transversely.